Pengaruh Employee Engagement, Pemberdayaan, dan Komitmen Organisasi Terhadap Kinerja Karyawan PT. Toyota Motormanufacturing Indonesia - Adel Christian P Sakeru; Aji Hermawan; Yunus Triyonggo (Universitas Airlangga, 2019)
PT Toyota Motor Manufacturing Indonesia needs to possess quality and competent human resources in order to face the stiff competition with the continuous growth of similar companies. Human resources development in a company must be well performed and well planned, and one way to do so is by performing evaluations about employee engagement, empowerment, and organisational commitment so that employees’ performance can be improved continuously, which in turn will improve the employees’ prosperity and the company’s profit. The purpose of this research is to analyse the impact of employee engagement, empowerment, and organisational commitment on the employees of PT. Toyota Motor Manufacturing, Indonesia’s human resources division. The data analysis method utilised in this research is the Structural Equation Model (SEM) with the Partial Least Squares (PLS) method, which uses the SmartPLS software. The result of this research is that empowerment and organisational commitment have a significant and positive impact on employees’ performance. Furthermore, employee engagement and empowerment also have a significant and positive result on organisational commitment. Employee engagement does not have a significant impact on employee performance, but it has a positive impact on employee performance. It shows that employee engagement does not have a direct impact, but it has an indirect impact on employee performance through organisational commitment.